Is two always better than one? Customer perception on the merger of startup decacorn companies - Ilham Fauzan Putra; Nila Armelia Windasari; Gita Hindrawati; Prawira Fajarindra Belgiawan (Journal of Open Innovation: Technology, Market, and Complexity, 2021)
Recently, the two decacorn Startups in Indonesia decided to collaborate with a merger scheme and accumulate over 100 million monthly active users. The Merger triggers a new perception for customers and has an impact on the level of Brand Loyalty. However, no research examines how customer perception to mergers between the startup with decacorn status. Therefore, this study intends to fill this gap. Using the mix method approach, this study investigates how customer perception of startups' mergers decacorn status and examines its effect on customer behavior. The findings revealed that customer self-congruency successfully mediates the research gap between customer perceptions on merger scheme (sig. 0.000 < 0.05, Ø = 0.575) and purchase intention (sig. 0.000 < 0.005, Ø = 0.390) by combining impulse buying strategies (sig. 0.003 < 0.05, Ø = 0.329). The paper contributes theoretically to the body of knowledge in the customer's perception of the merging company. The study also gives new insight that customers' perception of the Merger of two decacorn companies cannot guarantee that customers will be loyal to the company without connecting the customer self-congruency in each partner. It is recommended that the manager gain stimulus in building conformity of company image with customer perceptions that create self-congruency.
Keywords: 650; brand loyalty; customer perception; customer self-congruency; impulse buying; merger and acquisition; purchase intention; startup